Current status of imaging of Sjogren's syndrome. Issue 6 (December 2020) - Jousse-Joulin, Sandrine; Coiffier, Guillaume
Abstract: Primary Sjögren's syndrome (pSS) is an autoimmune disease, which involves salivary glands (SG) and extra glandular organs. Today, Sjögren's patients' diagnosis is based on classification criteria taking into account five objective tests, including histology, immunology, two ophthalmological tests, and salivary flow evaluation. To date, the challenge is to find the right imaging tool for diagnosis, follow up, and prognosis of pSS. The objective of this review is to describe as to what are these imaging modalities and particularly the place and validity of salivary glands ultrasonography (SGUS) in the diagnosis and follow-up strategy of patients with suspected pSS. Moreover, new noninvasive tools are emerging, including elastography, a new ultrasonography technique that provides an estimate of tissue elasticity, MRI, MR sialography, and 18 fluorodeoxyglucose–positron emission tomography. Although new imaging opportunities are available, SGUS should be the first-line choice in pSS because of its accessibility, feasibility over time, and sensitivity to change.